High strength inert ceramic balls - Sutjipto, Agus Geter Edy; Mohd Hasbi, Ab. Rahim; Nurjannah, Salim; Anwaruddin, Hisyam; Hanafi, Ani; Abd Razak, Ahmad (2021)
To develop sintered inert ceramic (balls) from Malaysian clays to meet industrial requirement for Malaysian oil and gas industries, oleochemical, fertilizer, gas processing and acid separation.